Effects of Different Cooking Methods on the Contents and Activities of Active Substances in Shiitake Mushroom Digested in Vitro in Simulated Gastrointestinal Juices - YAO Fen, LIU Hongxia, FAN Xiuzhi, SHI Defang, YIN Chaomin, GAO Hong, ZHANG Yu, YAO Wang (Shipin Kexue)
This study investigated the effects of different cooking methods and durations on the contents and activities of bioactive compounds in shiitake mushroom digested in vitro in simulated gastrointestinal juices. The contents of total phenols, total flavonoids, crude polysaccharide and eritadenine in steamed, boiled, air fried, or roasted mushroom digested in vitro in simulated gastrointestinal juices were determined, as well as their in vitro antioxidant, hypolipidemic and hypoglycemic activities. Furthermore, the correlation between the contents of bioactive compounds and the in vitro activities of the digests was analyzed. The results showed that compared with steaming, boiling, and air frying, roasting was more conducive to the retention of the four bioactive substances in shiitake mushroom. The contents of total phenols, total flavonoids and crude polysaccharides in the sample roasted for 5 minutes and the content of eritadenine in the sample roasted for 15 minutes were the highest, which were (222.13 ± 3.57) mg/g, (4.49 ± 0.06) mg/g, (5.57 ± 0.28) g/100 g and (551.31 ± 3.76) mg/100 g, respectively. After in vitro gastrointestinal digestion, the release of bioactive compounds from roasted mushroom was the highest, followed by air fried mushroom. The release of total flavonoids decreased with roasting time, while the release of all other bioactive substances had no significant correlation with cooking time. The in vitro activity of the simulated intestinal digest of steamed mushroom was the highest. The 1,1-diphenyl-2-picrylhydrazyl (DPPH) radical scavenging capacity of the in vitro intestinal digest of shiitake mushroom steamed for 20 minutes and the 2,2’-azino-bis(3-ethylbenzothiazoline-6-sulfonic acid) (ABTS) radical cation scavenging capacity of the in vitro intestinal digest of shiitake mushroom steamed for 10 minutes were the highest (P 0.05) in the α-glucosidase inhibitory activity of the intestinal digests of shiitake mushroom cooked by different methods. The highest pancreatic lipase inhibitory activity of (49.42 ± 2.32)% was found in the intestinal digest of shiitake mushroom steamed for 10 minutes (P > 0.05). The results of correlation analysis showed that the α-glucosidase inhibitory activity of the gastric digest was significantly positively correlated with the contents of total phenols (P < 0.01) and eritadenine (P < 0.05), while the ABTS radical cation scavenging capacity was significantly positively correlated with the contents of total phenols (P < 0.05) and crude polysaccharides (P < 0.01). The pancreatic lipase inhibitory activity of the intestinal digest was significantly negatively correlated with the contents of all four bioactive substances (P < 0.01). In summary, roasting was more conducive to the retention and digestive release of bioactive substances, while steaming was more conducive to improving the in vitro activity of simulated digested shiitake mushroom. This study provides guidance for the scientific and rational processing of shiitake mushroom.